Normalistas’ Written Performance in Workshops based on the Task Based Approach - Ciprian Castillo, Clemencia Caterine; Farfán Briceño, Diana María; Ramos Holguín, Bertha (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This research was developed with Complementary Training Program students – normalistas- at Escuela Normal Superior Santiago de Tunja. Its core purpose was to analyze and describe what the implementation of writing workshops under the task based approach for a group of Complementary Training Program students revealed about their written performance. This qualitative action research used interviews, students’ artifacts and field notes to gather information. Findings revealed that workshops helped students to strengthen their performance in several aspects such as vocabulary, grammar and structure and contributed to the students’ language development in the communicative field.